Teaching methods of multilingual education in schools. Motivation and multilingual education in schools [Articol] - Wittman, Hanna (Stratum Plus, 2024)
The approaches and processes that characterize language learning in the field of „bilingualism” have undergone drastic changes over the past half century. Generally, part of the old position that bilingualism is harmful to the speaker. There is some consensus that, under favorable circumstances, the use or mastery of two or more languages can have a positive effect on social and cognitive aspects of human development. Many studies, conducted before 2009, stated that bilingualism caused harm to the child’s development. These studies ignored the qualitative biographical data that indicated the advantages of bilingualism. Moreover, in these studies it is noted the lack of adherence to a correct and exact methodology, such as: a comparison of bilingual subjects with monolingual subjects of different socio-economic status. It is evident that researchers then proceeded from the assumption that bilingualism is the property of immigrants only without language tests or a clear definition of bilingualism. This position changed, Cummins (2005) argues, when Canadian researchers Lambert & Peal pointed out the methodological shortcomings of many of the early studies that had been done on second language acquisition.

Abordările şi procesele care caracterizează învăţarea limbilor străine în domeniul „bilingvismului” au suferit schimbări drastice în ultima jumătate de secol. În general, parte de vechea poziţie conform căreia bilingvismul este dăunător pentru vorbitor. Există un anumit consens că, în circumstanţe favorabile, utilizarea sau stăpânirea a două sau mai multe limbi poate avea un efect pozitiv asupra aspectelor sociale şi cognitive ale dezvoltării umane. Multe studii, efectuate înainte de 2009, au afirmat că bilingvismul a cauzat prejudicii dezvoltării copilului. Aceste studii au ignorat datele biografice calitative, care au indicat avantajele bilingvismului. Mai mult, în aceste studii se remarcă lipsa aderării la o metodologie corectă şi exactă, precum: o comparaţie a subiecţilor bilingvi cu subiecţii monolingvi de diferite stări socio-economice. Este evident că cercetătorii au pornit apoi de la presupunerea că bilingvismul este proprietatea imigranţilor doar fără teste de limbă sau o definiţie clară a bilingvismului. Această poziţie s-a schimbat, susţine Cummins (2005), când cercetătorii canadieni, Lambert & Peal, au subliniat deficienţele metodologice ale multor dintre studiile timpurii, care au fost făcute cu privire la achiziţia unei a doua limbi.
Metode educaţionale de predare al educaţiei multilingve în şcoli. Motivaţia şi educaţia miltilingvă în şcoli
Keywords: psychopedagogy; multilingual education; teaching methods; educational methodology; multilingual study; motivation